Intelligent Drug Delivery Systems Based on Modified Chitosan Nanoparticles - R. Saboktakin, Mohammad; A. Tabar, Neda; M. Tabatabaie, Roya; Maharramov, Abel; A. Ramazanov, Mohammad (Letters in Organic Chemistry, 2012)
The purpose of this review is to discuss and summarize some of the interesting findings and applications of modified chitosan (MCS) and their derivatives in different areas of drug delivery. This review highlights the important applications of MCS in the design of various novel delivery systems like liposomes, microspheres, microcapsules, and nanoparticles. In addition to their well-known effects on drug solubility and dissolution, bioavailability, safety, and stability, their uses as recipients in drug formulation are also discussed. This review also focuses on various factors influencing inclusion complex formation because an understanding of the same is necessary for proper handling of these versatile materials. Some important considerations in selecting MCS in drug formulation such as their commercial availability, regulatory status, and patent status are also summarized.
Keywords: Polymers